Dinamika Pengetahuan Akuntansi, Pengalaman Usaha, dan Motivasi Kerja: Analisis Penggunaan Laporan Informasi Akuntansi oleh Pelaku UMKM di Kota Lhoksukon - Ismaulina, Ismaulina (Jurnal Ilmu Manajemen, 2024)
Understanding the influence of accounting knowledge, business experience and work motivation on the use of accounting information reports by Lhoksukon City MSMEs is essential to promote business effectiveness and continuity. This study is directed at examining the interaction between accounting knowledge, business experience, and work motivation in the context of the use of accounting information reports, with the aim of providing a new perspective regarding these elements interacting to support business decisions. Using quantitative methods, questionnaires were distributed to 74 MSMEs from a total of 291 MSMEs in Lhoksukon, and analyzed using multivariate statistics to identify relationships and influences between variables. The research results show: Adequate accounting knowledge, extensive business experience and high work motivation contribute significantly to the intensity of use of accounting information reports in making business decisions. The importance of work motivation as a mediator that strengthens the effect of accounting knowledge and business experience on the use of accounting information is also identified. These findings underline the need for training and education programs that focus on increasing accounting knowledge for MSMEs and building work motivation as a basis for the effective use of accounting information in business activities. This research makes a significant contribution to the MSME accounting and management literature, as well as providing practical guidance for policy makers, educational institutions and MSME actors in designing capacity development strategies and work motivation to maximize the benefits of accounting information for business success.